2021
DOI: 10.3389/fpsyg.2021.708037
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Study of Gambling Behaviors During the COVID-19 Pandemic in Sweden

Abstract: This study aimed to investigate changes in gambling behaviors during the first and second waves of the COVID-19 pandemic in Sweden. Participants who had gambled within the past year were recruited from social media and the Swedish National Helpline (n = 325, mean age 39.8 years, 64.8% males, 31.3% with problem gambling) and completed an online survey measuring gambling behaviors, consequences of the pandemic in general and worries related to the pandemic. A sub-sample (n = 139) completed a follow-up survey, du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…The immoderate and improper use of mobile phones as well as of the Internet can also lead adolescents to withdraw from others, to develop relational insecurities or to nurture a fear of rejection, to feel inadequate and in need of support, even if it is external and an end in itself. It should not be forgotten that among these forms of addiction, there is also what is known as ludopathy, i.e., addiction to games and gambling, to which mobile devices also contribute on a large scale (110)(111)(112).…”
Section: Discussionmentioning
confidence: 99%
“…The immoderate and improper use of mobile phones as well as of the Internet can also lead adolescents to withdraw from others, to develop relational insecurities or to nurture a fear of rejection, to feel inadequate and in need of support, even if it is external and an end in itself. It should not be forgotten that among these forms of addiction, there is also what is known as ludopathy, i.e., addiction to games and gambling, to which mobile devices also contribute on a large scale (110)(111)(112).…”
Section: Discussionmentioning
confidence: 99%
“…The immoderate and improper use of mobile phones and the Internet not only can cause huge gaps between people, but can also lead them to withdraw into themselves, to develop relational insecurities or a fear of rejection, to feel inadequate and in need of support, even if this is external and for its own sake. It should not be forgotten that among these forms of addiction, there is also the so-called ludopathy, i.e., addiction to games and gambling, to which mobile devices also contribute on a large scale ( 95 , 96 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to the results of the present study, almost half of all respondents used the first lockdown to cease participation in higher-risk forms of gambling at least for a medium-term period (until the second lockdown). A Swedish study reported much lower rates of quitters of riskier forms of gambling during the first lockdown (<10%) ( Månsson et al, 2021 ). However, these varying results may be due to the composition of the respective online panels or to specific lockdown rules.…”
Section: Discussionmentioning
confidence: 99%